Proposal to categorize coefficients of variation for yield and plant height in soybean - Carvalho, Claudio Guilherme Portela de; Arias, Carlos Alberto Arrabal; Toledo, José Francisco Ferraz de; Almeida, Leones Alves de; Kiihl, Romeu Afonso de Souza; Oliveira, Marcelo Fernandes de; Hiromoto, Dário Minoru; Takeda, Claudio (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to define categories for the coefficients of variation obtained in soybean plant height and yield. The experimental data were obtained in intermediary and final (regional) adaptation trials carried out in the States of Paraná and Mato Grosso. Different categories were established for each State and maturity group. Taking the mean and the standard deviation of the coefficients of variation obtained from the analyses of variance of the experiments, the coefficients of variation were classified as low, average, high and very high. An additional classification was made using the median and pseudo-sigma as substitutes for mean and standard deviation, respectively. The classification for the coefficients of variation depended on the trait and the location but did not vary greatly for each maturity group. The adopted criteria (mean and standard deviation or median and pseudo-sigma) were similar (regardless of the coefficient of variation distribution), and satisfactory in determining the experimental accuracy. The maximum acceptable limits for coefficient of variation are 16% and 12% for yield and plant height, respectively.
Keywords: Glycine max; yield components; statistical analysis